Study on the Mechanical Characteristic of Special-shaped Asymmetric Flexure Hinge - Cheng Li; Chuanli Wang; Tao He; Huanyu Huo (Jixie chuandong)
Based on the design concept of hybrid flexure hinge with large flexibility， an asymmetric hybrid flexure hinge with straight circle cycloid is proposed， and its mechanical characteristics are studied. Based on the bending theory of cantilever beam and Hooke's law under the micro element method， by selecting the appropriate integral variable and intermediate variable， the relatively simple calculation formula of rotational flexibility and tensile flexibility is obtained， and the general calculation formula of the maximum stress is given. The variation trend of rotational flexibility and maximum stress with parameters is discussed. The influence degree of structural parameters on rotational flexibility and maximum stress is compared. The results show that the maximum errors of the analytical expressions of rotational flexibility， tensile flexibility and maximum stress are within 5%， 7% and 5%， respectively. The rotational flexibility is inversely proportional to the elastic modulus， width and minimum thickness， and is directly proportional to the straight circle radius and arch height parameters， and is most sensitive to the change of the minimum thickness， followed by the width， and the arch height and straight circle radius are the weakest. The maximum stress is inversely proportional to the width， minimum thickness and the radius of the straight circle， and it is most sensitive to the change of the minimum thickness， followed by the width， and the radius of the straight circle is the weakest.